2003
DOI: 10.1590/s0074-02762003000300021
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of tumor necrosis factor-alpha in asymptomatic/"indeterminate" and Chagas disease cardiomyopathy patients

Abstract: We compared plasma tumor necrosis factor-α (TNF-α) levels among asymptomatic/"indeterminate" Chagas disease patients (ASY)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
98
3
13

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 22 publications
9
98
3
13
Order By: Relevance
“…Impairment of the Th1 immune response is involved in susceptibility to several infections, especially by fungi, viruses, intracellular bacteria and even by protozoa, such as Leishmania sp. Other studies, analyzing levels of serum cytokines, have demonstrated that TNF-α levels are significantly higher in Chagas' disease patients compared to normal controls 9 , while other work has pointed to undetectable levels of TNF-α and IFN-γ levels that did not differ from those of the controls 22 .…”
Section: Resultsmentioning
confidence: 97%
“…Impairment of the Th1 immune response is involved in susceptibility to several infections, especially by fungi, viruses, intracellular bacteria and even by protozoa, such as Leishmania sp. Other studies, analyzing levels of serum cytokines, have demonstrated that TNF-α levels are significantly higher in Chagas' disease patients compared to normal controls 9 , while other work has pointed to undetectable levels of TNF-α and IFN-γ levels that did not differ from those of the controls 22 .…”
Section: Resultsmentioning
confidence: 97%
“…Similar high levels of TNF-α were detected in asymptomatic individuals and patients with digestive and CARD clinical forms, respectively (Perez-Fuentes et al 2007). However, Ferreira et al (2003) showed that patients with significant left ventricular (LV) dysfunction (LV ejection fraction ≤ 50%) showed higher levels of TNF-α, compared to chagasic patients without LV dysfunction. It has been suggested that chronic TNF-α production prior to heart failure may play a role in chronic Chagas disease cardiomyopathy progression (Ferreira et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, Ferreira et al (2003) showed that patients with significant left ventricular (LV) dysfunction (LV ejection fraction ≤ 50%) showed higher levels of TNF-α, compared to chagasic patients without LV dysfunction. It has been suggested that chronic TNF-α production prior to heart failure may play a role in chronic Chagas disease cardiomyopathy progression (Ferreira et al 2003). A similar level of cytokine production in sera of acute chagasic children, compared to NI, has been described previously (Moretti et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCC patients had higher levels of TNF- and CCL2 than indeterminate patients (Ferreira, et al, 2003, Talvani A., et al, 2004 (Reddy, et al, 2008, Riol-Blanco, et al, 2005, Sakai, et al, 2006.…”
Section: The Cytokines and Chemokinesmentioning
confidence: 89%